Student Perceptions of Andalas University Payakumbuh Campus Against the Speed of Access to Academic Information Systems - Yindrizal Yindrizal; Susiana Susiana; Erizal.N Erizal.N; Melkia Zahra; Olivia Vransiska Cania (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
The need for information continues to grow rapidly such as the need for an Academic Information System, where Academic Information System is an innovation of technology and information. This happens because of the demands of the times that require information to be transferred quickly. To find out how fast information reaches users who are the main goal, the parameters used are bandwidth and signal strength. The access speed of an information system network is one of the dimensions that is very important for users of the information system. The results of the study state that the Academic Information System of Andalas University access is quite good at normal usage times, but often hangs or errors at peak usage times, both access is done with a computer or laptop or with a smartphone.